PREPARATION AND EVALUATION OF SIMVASTATIN TRANSDERMAL FILM - Anod, Haritha V.; Gupta, N. Vishal; Gowda, D. V.; M., Manohar (International Journal of Applied Pharmaceutics, 2018)
Objective: The objective of the study was to prepare simvastatin transdermal films for the treatment of atherosclerosis and to evaluate the effect of concentration of polymer on penetration enhancement. Methods: Solvent evaporation technique was employed for the preparation of films and the prepared films were evaluated for various physicochemical properties of films such as tensile strength, thickness, surface pH, swellability, drug content, moisture content and folding endurance. In vitro drug, release study and release kinetics were also studied. Results: Tensile strength ranged from 3.56±0.343 to 4.56±0.12 (N/mm²). The films were of uniform weight. Thickness varied from 0.2±0.3 mm to 0.2±0.8 mm. Surface pH ranged from 6.6±0.14 to 6.9±0.16. Percentage swellability ranged from12.1±0.36 to 16.3±0.22. Percentage drug content ranged from 88.4±0.7% to 90.5±0.6% in all the formulation. Percentage moisture content ranged from 0.864 to 1.03%. Moisture uptake was from 2.6±0.24 to 2.9±0.072. The folding endurance test gave satisfactory results and F3 formulation showed maximum drug release. Conclusion: From the study, it was concluded that out of various formulations, the F3 formulation was found to be the optimum formulation with 88% drug release at the fourteenth hour.